The influence of the parallel programming on the performance of cryptographic algorithms - Kraska, Mateusz; Kozieł, Piotr (Journal of Computer Sciences Institute, 2016)
Paper compares possibility to parallelize two cryptographic algorithms: Xor cipher and MD5 collision search. Presented solutions allows user to specify number of used processors. Performance of algorithms where tested on a different types of processors and visualized on graphs.